ECONOMIC MELTDOWN: AN EXAMINATION OF COUNTRY-TOCOUNTRY EXPERIENCES AND POLICY OPTIONS - Iyeli, Iyeli I.; Effiom, Lionel; Oshi, J.E.O (EBSU Journal of Social Sciences and Humanities, 2022)
The 2008 global economic meltdown has its origin largely in the flawed policies of the American government in the last 10 years and the extravagant lifestyles which their system seemed to encourage. When their financial system melted, it reverberated across the globe. Most developed countries acted individually to put in place some emergency measures to stop further slide and cushion, as it were, their people from the effects of the crisis. The top industrialised economies under the G-20 also came together to take harmonised or unified actions against the perceived causes of the meltdown. Their objectives were to avoid such major dislocations in the future and coordinate such actions so that they are not at cross purposes between their members. This study attempted a contrast of these measures with ones taken by Nigeria where top government officials are still not in agreement as to the impact of the meltdown on our economy. It reviewed some of these haphazard actions of the Nigerian government and concluded that if developed countries succeed in coming out of the recession, it would not be by luck; rather it will be the outcome of pre-meditated actions calculated to jolt the economy back into life. In contrast, if the Nigerian economy bounces back, it will not be because its leadership took any fundamental actions to make it happen. It recommends a fundamental shift for the Nigerian economic managers and other less developed countries of the need to gather data, develop and implement strategic plans that will see the country out of the woods.